How Millennials and Generation Z organise travel during the COVID-19 pandemic - Perčić, Karolina; Spasić, Nada (Hotel and Tourism Management, 2021)
The subject of the paper is the consumer behaviour of Millennials and Generation Z as travellers in organising their travel. Through empirical research, conducted with online questionnaire in May 2021, the paper focuses on the way the above-mentioned generations in Serbia have organized travel (through a travel agency or on their own) before and during the COVID-19 pandemic, as well as the choice of accommodation during the pandemic, and the respondents’ opinions on travel with COVID-19 passports. The aim of this paper is to discover the preferences and opinions of travellers when organizing travel under the new circumstances, as well as examining whether there are differences in the behaviour of Millennials and Generation Z as travellers before and during the pandemic, in order to provide significant information for the marketing decision making of tourism and hospitality organisations. Almost a quarter of the world’s population is made up of Millennials, who, along with Generation Z, make up the current and future force that contributes the most to the income generation. Members of this population in Serbia are less and less opting for the services of travel agencies, especially during the pandemic, while the number of passengers of these generations who organize self-directed travel is on the increase. Quantitative statistical methods – descriptive statistics (frequency distribution) and comparative statistics (Pearson ?2-test) were used for analysis of the obtained research results.